Profile Analysis of Students’ Critical Thinking Skills in Integrated Biology Learning - Masru'ah, Masru'ah (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
Critical thinking is the ability to think reasonedly and reflectively. It emphasizes making decisions about what to believe or do. So, students must have the ability to be able to compete in the industrial revolution 5.0 era. This research aims to describe students' critical thinking skills in integrated biology learning on biodiversity material. This research is exploratory research with a qualitative and quantitative descriptive approach. The objects in this research were 109 students of class X MAS Raudlatul Ulum for the academic year 2023/2024. Data collection was carried out using test methods (multiple choice and essay), observation, and interviews. The test questions are arranged according to indicators of critical thinking skills namely; interpretation, analysis, evaluation, and inference. The result shows that students' critical thinking skills are not good category. The results of observations and interviews show that students are not yet able to analyze questions independently, process and conclude the various information they obtain, and they do not yet have the confidence to express the opinions or thoughts they have. The varied abilities of students also influence the research findings, because the research subjects are new students from various junior high schools who have diverse educational backgrounds and educational systems. Based on the result, teachers should train and familiarize students with being able to think critically through various effective and efficient learning processes.